Blood pressure and vascular determinants of glomerular filtration rate decline in diabetic kidney disease - Truscello, Luca; Nobre, Dina; Sabaratnam, Vehashini; Bonny, Olivier; Wuerzner, Grégoire; Burnier, Michel; Fakhouri, Fadi; Pruijm, Menno; Zanchi, Anne (Frontiers in Cardiovascular Medicine, 2023)
Objective: In patients with type 2 diabetes and diabetic kidney disease (DKD), explore the relationship between estimated glomerular filtration rate decline (eGFR-d) and simultaneously assessed vascular risk markers including office, ambulatory or central blood pressure, pulse pressure, carotid-femoral pulse wave velocity (PWV), carotid intima-media thickness (IMT) and renal resistive indexes (RRI).: At baseline, vascular risk markers were measured in addition to the routine clinical workup. The eGFR-d was based on 2000-2019 creatinine values. Parameters were compared by eGFR-d quartiles. Regression models of eGFR-d and vascular markers were assessed.Results: In total, 135 patients were included. Mean age was 63.8±10.8y, baseline eGFR 60.2±26.4ml/min/1.73m 2 and urine albumin-creatinine ratio (ACR) 49±108 mg/mmol. Mean eGFR-d was based on 43±39 creatinine values within a time span of 7.0±1.9y. The average yearly eGFR decline was -1.8±3.0ml/min/1.73m 2 ranging from -5.8±2.3 in the first quartile to +1.4±1.7 in the fourth quartile. Mean 24h systolic (SBP) and diastolic (DBP) blood pressure were 126±17 and 74±9mmHg.Mean PWV was 11.8±2.8 m/s, RRI 0.76±0.07 and IMT 0.77±0.21mm. SBP and pulse pressure correlated with eGFR-d but not DBP. 24h SBP stood out as a stronger predictor of eGFR-d than office or central SBP. PWV and RRI correlated with eGFR decline in univariate, but not multivariate regression models including 24 SBP and ACR.Conclusions: In this study, eGFR decline was highly variable in patients with type 2 diabetes and DKD.